Elite freestyle wrestlers` competitive performance analysis - Efremov, V.V.; Kolodeznikova, M. G.; Nikolaev, N. D. (Theory and Practice of Physical Culture, 2017)
The article analyses competitive performance of elite freestyle wrestlers in 2015 World Championship (WC) in Las Vegas, 2015 European Games (EG) in Baku and 2015 Golden Grand Prix in Baku. The analysis of the freestyle wrestlers` competitive performance records made it possible to range their key competitive technical and tactical actions and profile the individual competitive performance of each wrestler with every action frequency, success and dependability rates in typical competitive situations. It should be noted that the elite wrestlers tend to be highly rational in their competitive techniques that means that most of them tend to avoid the moves potentially fraught with a risk of point deduction including high crotches over the head ("mills"), ankle picks, trips, hip-rolls and drop-backs. In stand-up positions, the wrestlers were found to prefer leg takedowns; and in referee`s position - turnovers and stretchers.